Digital Technology Training in Developing Teaching Modules Based on Sumbawa Local Wisdom - Ramdhayani, Eryuni; Noviati, Wiwi; Walidain, Sri Nurul (Unram Journal of Community Service, 2025)
The implementation of the Independent Curriculum in Indonesia encourages educators to be more creative and innovative in preparing teaching modules. Especially in areas with a wealth of local wisdom such as the Sumbawa highlands, the integration of local values ​​into the learning process is very important to create meaningful and holistic learning. However, the lack of teacher skills in designing teaching modules that are interesting, interactive and appropriate to student characteristics is a problem that needs to be resolved. This service activity aims to provide training to teachers in using digital technology to develop teaching modules based on local wisdom. The method used in this service is carried out in a structured manner with training and mentoring activities. The procedural stages of the activities are carried out in several stages, namely preparation, implementation and evaluation. Participants in this training consisted of 18 teachers at SMPN 4 SATAP Moyo Hulu. The results of this service activity showed that the pretest and posttest results given to teachers went from 61% to 85%, there was an increase in teacher knowledge by 24%. Participants arrived on time and participated in the activities 85% fully. The results of the task of preparing teaching modules based on local wisdom collected were 85%. From the community service activities that have been carried out, it can be concluded that the activities have been effective, seen from the participants' increased knowledge in preparing local wisdom-based teaching modules in the independent curriculum and their skills in designing local wisdom-based teaching modules have increased.